Децентралізація влади в Україні: конституційно-правовий аспект : автореферат дисертації - Чорнописький, П. Б.; Chornopyskyi, P. B.; Марцеляк, О. В. - науковий керівник (Харків, 2018)
Дисертація є комплексним науковим дослідженням децентралізації влади в Україні. У роботі розкрито правову природу конституційної реформи як феномена цивілізаційного розвитку і фактора сучасного державотворення, яка виступає ключовою основою розпочатої в Україні децентралізації влади. Проаналізовано існуючі в науці конституційного права підходи до розкриття правової природи децентралізації влади та зроблено висновок, що повною мірою охарактеризувати цей феномен можна з точки зору аналізу децентралізації влади за формою, змістом і суттю. Досліджено сучасні конституційні реформи в країнах Європи у сфері місцевого самоврядування і децентралізації влади як приклад для України. Відстоюється позиція, що успіх розпочатої в Україні реформи у сфері децентралізації влади залежить, насамперед, від удосконалення територіального устрою України і модернізації національної моделі механізму публічної влади. У результаті дослідження автором запропоновано модель адміністративно-територіального устрою України, шляхи подальшого розвитку й удосконалення конституційно-правового статусу органів місцевого самоврядування та органів виконавчої влади на місцях, напрацьовано конкретні пропозиції з модернізації чинного законодавства, які прискорять реформу у сфері децентралізації влади в Україні.

The thesis is a comprehensive academic research of decentralization of power in Ukraine. This issue is researched via revealing a legal nature of constitutional reform as a phenomenon of civilizational development and a factor of contemporary state building. It is stated that a priority direction of the constitutional reform in Ukraine is decentralization of public authorities in the country. The existing constitutional law science approaches to revealing a legal nature of power decentralization are analyzed, and the conclusion is made that this phenomenon may be characterized to the full extent in terms of power decentralization analysis by form, content, and essence. The candidate for a degree maintains a position that the reform of power decentralization in Ukraine depends on improvement of the state territorial division, which should cover, firstly, establishment of communities that will be a primary unit in a system of administrative and territorial division of Ukraine; secondly, enlargement of districts; thirdly, regionalization of Ukraine. The thesis also states that a key role in the power decentralization in Ukraine should be assigned to modernization of the national public authority mechanism model. This modernization should primarily start with development and creation of appropriate legal framework for improvement of status of territorial communities and local self-government bodies, election of the most efficient model of local executive bodies, liquidation of existing district and regional state administrations and establishment of new institutions, namely state representative offices headed by prefects with solely supervising and coordinating, and not the executive functions. Particular characteristic of contemporary state and prospects for constitutional reform implementation in the area of power decentralization in Ukraine lead to the conclusion on the need of domestic legislation improvement. Immediate introduction of amendments to the Constitution, adoption of the Municipal Code of Ukraine, the Laws of Ukraine "On the Principles of the Administrative and Territorial Division of Ukraine", "On Prefects and State Representative Offices", etc. will promote establishment of Ukraine as a democratic, legal, and social state.

Диссертация представляет собой комплексное научное исследование децентрализации власти в Украине. В работе освещена правовая природа конституционной реформы как феномена цивилизационного развития и фактора современного государственного строительства, которая выступает основой начатой в Украине децентрализации власти. Анализируются существующие в науке подходы понимания децентрализации власти и делается вывод, что надлежащим образом охарактеризовать ее можно через призму понимания децентрализации по форме, содержанию и сущности. Исследуются современные конституционные реформы в странах Европы в сфере местного самоуправления и децентрализации власти как пример для Украины. Отстаивается позиция, что успех начатой в Украине реформы по децентрализации власти зависит в первую очередь от усовершенствования территориального устройства Украины и модернизации национальной модели механизма публичной власти. В результате исследования автором предложена модель административно-территориального устройства Украины, пути дальнейшего развития и совершенствования конституционно-правового статуса органов местного самоуправления и органов исполнительной власти на местах, разработаны конкретные предложения по модернизации действующего законодательства, которые ускорят реформу в сфере децентрализации власти в Украине.
Keywords: Україна; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.02; Конституція України; конституційна реформа; децентралізація влади; місцеве самоврядування; адміністративно-територіальний устрій; регіоналізація; префект; органи виконавчої влади на місцях; Constitution of Ukraine; constitutional reform; decentralization of power; local government; territorial system; prefect; local executive bodies; Конституция Украины; конституционная реформа; децентрализация власти; местное самоуправление; административно-территориальное устройство; регионализация; органы исполнительной власти на местах